A Comprehensive Study on the Application of Reverse Osmosis (RO) Technology for the Petroleum Industry Wastewater Treatment - Shahryar Jafarinejad (Journal of Water and Environmental Nanotechnology, 2017)
Large quantities of oily wastewaters can be generated from the activities and processes in the petroleum industry which draining of these effluents not only pollutes the environment but also reduces the yield of oil and water. Therefore, development of treatment processes for petroleum industry wastewaters is vital in order to prevent serious environmental damage and provide a source of water for beneficial use. Reverse osmosis (RO) can be the most common membrane process used for desalination from oily wastewater and can produce water suitable for reuse at the petroleum industry. In this study, the application of RO technology for the petroleum industry wastewater treatment in different laboratory, pilot, field, and industrial scales have been reviewed. In addition, membrane fouling control, performance efficiency, treatment system configurations, pretreatment methods, quality of treated water, and economic issues have been investigated. With mixtures as complex as petroleum industry wastewaters, membrane fouling becomes a significant hurdle to implement the RO-based purification system. Operating the system within the critical flux range or adding chemicals, and/or pretreatment can usually control membrane fouling. Salt rejection of RO membranes can be 99% or higher.